2013
DOI: 10.1128/iai.00054-13
|View full text |Cite
|
Sign up to set email alerts
|

Flagellar Motility Is a Key Determinant of the Magnitude of the Inflammasome Response to Pseudomonas aeruginosa

Abstract: eWe previously demonstrated that bacterial flagellar motility is a fundamental mechanism by which host phagocytes bind and ingest bacteria. Correspondingly, loss of bacterial motility, consistently observed in clinical isolates from chronic Pseudomonas aeruginosa infections, enables bacteria to evade association and ingestion of P. aeruginosa by phagocytes both in vitro and in vivo. Since bacterial interactions with the phagocyte cell surface are required for type three secretion system-dependent NLRC4 inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
64
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 39 publications
4
64
0
1
Order By: Relevance
“…G. O'Toole and D. Hogan (Dartmouth Medical School, Hanover, NH). The popB mutant has been previously described (35).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…G. O'Toole and D. Hogan (Dartmouth Medical School, Hanover, NH). The popB mutant has been previously described (35).…”
Section: Methodsmentioning
confidence: 99%
“…This leads to pro-IL-1␤ processing and release as mature IL-1␤. Loss of a functional bacterial T3SS or any of the NLRC4 inflammasome components, namely NLRC4, caspase-1, and ASC, leads to a deficit in IL-1␤ production by macrophages in response to P. aeruginosa (16,28,35,43).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2). Flagellar motility is important for inflammasome activation independently of the flagellin protein, and pilin may also activate the inflammasome in P. aeruginosa (33,34). To analyze the motility phenotypes of the chronic, acute, and environmental isolates in our study, we performed swimming (flagellar-based) and twitching (pili-based) motility assays.…”
Section: Cf Clinical Isolates Show Decreased Expression Of Inflammasomentioning
confidence: 99%
“…Multiple reports have demonstrated that flagellar function is a critical virulence factor for the establishment, persistence, and inflammatory profile of P. aeruginosa infection (1,2,19,28). P. aeruginosa swims via a single, polar, monotrichous flagellum, which it rotates by proton motive force (33).…”
mentioning
confidence: 99%